2017
DOI: 10.4172/2155-9929.1000323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of a Serum Protein Panel (FLNA, FLNB and KRT19) for Diagnosis of Prostate Cancer

Abstract: This study reports on the development of a novel serum protein panel of three prostate cancer biomarkers, Filamin A, Filamin B and Keratin-19 (FLNA, FLNB and KRT19) using multivariate models for disease screening and prognosis. ELISA and IPMRM (LC-MS/MS) based assays were developed and analytically validated by quantitative measurements of the biomarkers in serum. Retrospectively collected and clinically annotated serum samples with PSA values and Gleason scores were analyzed from subjects who underwent prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Our data show that both KLK3 and SORD were significantly overexpressed in PCa tissues. Both Filamin‐A (FLNA) and Filamin‐B (FLNB) were proposed as protein panel signatures for diagnosis of PCa (Narain et al ., ; Ravipaty et al ., ). FLNA was found to be downregulated in PCa tissues.…”
Section: Resultsmentioning
confidence: 97%
“…Our data show that both KLK3 and SORD were significantly overexpressed in PCa tissues. Both Filamin‐A (FLNA) and Filamin‐B (FLNB) were proposed as protein panel signatures for diagnosis of PCa (Narain et al ., ; Ravipaty et al ., ). FLNA was found to be downregulated in PCa tissues.…”
Section: Resultsmentioning
confidence: 97%
“…The genes containing ESRP-activated exons that were also activated by androgen exposure (Figure 4B) included: MINK1 (exon 18) which encodes a pro-migratory serine/threonine kinase; MAP3K7 (exon 12) which encodes a serine/threonine kinase that regulates signalling and apoptosis, activates NFKappaB, and is lost in aggressive prostate cancer (Kluth et al, 2013; Rodrigues et al, 2015); GRLH1 (exon 5) that encodes a transcription factor involved in epithelial cell functions (Jacobs et al, 2018); and FLNB (exon 30), alternative splicing of which has been identified as a key switch contributing to breast cancer metastasis (Li et al, 2018; Ravipaty et al, 2017). Amongst the genes containing ESRP2-repressed exons that were also skipped in response to androgen stimulation (Figure 4C) were DOCK7 (exon 23), which encodes a guanine nucleotide exchange factor involved in cell migration (Gadea and Blangy, 2014); and RPS24 (exon 5), a gene that is highly expressed in prostate cancer (Arthurs et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The two proteins play a major role in cell migration, vascular development, extracellular signaling and activity of integrins. 95,153 Filamin-A and androgen receptor (AR) association play a role in nerve growth factor (NGF) induced cell migration where it is known PCa is associated with the synthesis of large amounts of NGF which then stimulates tyrosine receptor kinase A (TrkA). 154 This is just one example of potential successful PCa biomarkers that have the possibility of identifying cancer quicker or preventing overdiagnosis within patients.…”
Section: Discussionmentioning
confidence: 99%